1986
DOI: 10.1037/0021-843x.95.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Initial symptom levels and the life-event–depression relationship.

Abstract: A sample of 93 persons selected for diversity of initial depression levels was studied longitudinally to explore the relation between stressful events and depression, both assessed with interview and selfreport methods. Previous research has often indicated modest associations but has been limited by methodological issues of assessment, sampling, and design, which are addressed in the present work.Regression analyses and inspection of individual patterns supported the hypothesis that initial depression status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 29 publications
4
74
1
Order By: Relevance
“…One of the studies from the Hammen et al (1985) project was our first to examine, among other hypotheses, the question of whether depression is associated with increased rates of dependent life events. We observed that students who had continuing depression over 6 months were more likely to have dependent event stressors compared to remitted and nondepressed groups (Hammen, Mayol, deMayo, & Marks, 1986). I also acknowledge a great debt to the influence of developmental psychopathology models in general (e.g., Rutter, 1986), and Bowlby's (1969) attachment theory in particular.…”
Section: Influence Of the Interpersonal Focusmentioning
confidence: 92%
“…One of the studies from the Hammen et al (1985) project was our first to examine, among other hypotheses, the question of whether depression is associated with increased rates of dependent life events. We observed that students who had continuing depression over 6 months were more likely to have dependent event stressors compared to remitted and nondepressed groups (Hammen, Mayol, deMayo, & Marks, 1986). I also acknowledge a great debt to the influence of developmental psychopathology models in general (e.g., Rutter, 1986), and Bowlby's (1969) attachment theory in particular.…”
Section: Influence Of the Interpersonal Focusmentioning
confidence: 92%
“…Hammen et al [32] found that nonsymptomatic persons were relatively resistant to the onset of depression even when exposed to high-impact stressful events, whereas those who were symptomatic continued to have both more depression and more high-impact events over time. In our study, we found recurrent episodes of major depression in 13% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that dysphoric persons respond with more depression following stressful life events than their more fortunate counterparts (Hammen, Mayol, DeMayo, & Marks, 1986;Lakey, Baltman, & Bentley, 1993;Monroe, 1982). Dysphoric persons may interpret events more negatively, respond with diminished social competence; or utilize less effective coping behaviors (Barnett & Gotlib, 1988).…”
mentioning
confidence: 98%